Long-term nitrogen amendments alter soil properties and diazotrophic communities in heavy metal-contaminated soils - Fangming Yu; Wenjie Wang; Pu Huang; Yue Yuan; Yingmei Xu; Jianing Gan; Yuehan Li; Rifeng Wu; Yi Li (Journal of Environmental Sciences, 2026)

Adsorption and immobilization of antimony (Sb) in aqueous and contaminated-soil by lanthanum-manganese modified biochar - Yi Li; Chijian Tang; Yu Gao; Ziang He; Fangming Yu; Rifeng Wu (Journal of Environmental Chemical Engineering, 2026)

Ginsenoside Rk1 reprograms ‘cold’ cancer cell membranes into a ‘hot’ antigen repertoire for highly immunogenic cancer vaccines - Fangming Dong; Linlin Qu; Lebin Wang; Jing Zhao; Zhiguang Duan; Xueqing Yu; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2026)

Enhanced phytoextraction of manganese and cadmium by Polygonum lapathifolium L. via Enterobacter sp. inoculation: Roles of rhizosphere regulation and endophytic microbiome assembly - Yi Li; Chijian Tang; Yinghao Mo; Yong Shan; Ziang He; Yaoheng Huang; Cuiping Wan; Rifeng Wu; Chunlai Zhang; Jiang Liang; Tongbin Zhu; Fangming Yu (Journal of Hazardous Materials, 2026)

Unraveling the stress regulatory mechanisms and biological roles of the novel RimI-ArsR type Ⅱ toxin-antitoxin system in Tetragenococcus halophilus CICC 10469 - Yu Zhang; Fangming Lan; Chi Zhao; Jvliang Dai; Dongdong Sun; Lixin Luo (Food Microbiology, 2026)

Resource‐Dependent Metabolic and Biogeochemical Consequences of Viruses in Agricultural Soils - Guixiang Zhou; Junxi Liu; Fangming Liu; Yu Xiao; Emily B. Graham; Yakov Kuzyakov; Mao Ye; Xiuli Xin; Lin Chen; Congzhi Zhang; Donghao Ma; Zongzhi Wu; et al. (Global Change Biology, 2026)
Soil viruses are crucial for microbial life, biogeochemical cycles of carbon and nutrients, and for microbial necromass formation. We hypothesized that the effects of viruses on these processes depend on organic matter and nutrient availability in soils. Here, we combined a 34‐year long‐term fertilization trial, 150 sequenced soil metagenomes, and microcosm experiments to explore how viruses modulate carbon and nutrient dynamics depending on resource availability. We uncovered 2789 viral populations (vOTUs) grouping into 301 viral clusters, 91% of which were previously unknown. Organically fertilized soils harbored most lytic viruses carrying diverse element cycling‐related auxiliary viral genes (AVGs) acquired through co‐evolution and horizontal gene transfer. Synthesis and heterologous expression assays further indicated that four AVGs (i.e., cbhA , pel , wbpD , GT2 ) had higher transcript levels in Escherichia coli under nutrient rich than nutrient poor conditions. Addition of virus particles to soils raised microbial carbon use efficiency (CUE; biomass production relative to carbon uptake) and accelerated microbial turnover leading to boosted microbial necromass formation by 14%. Conversely, in soils without organic fertilizers, viruses facilitate bacterial adaptation to stress (e.g., defense system and interference competition) and accelerate microbial decomposition of organic matter. 35 days after virus addition, CO 2 and N 2 O emissions increased by 41% and 52%, respectively. Finally, we propose the Viral Entombing‐Priming (VEP) framework to describe the contrasting roles of viruses in carbon and nutrient dynamics depending on soil fertility. This work reveals the viral “Matthew effect” ( the rich get richer and the poor get poorer ) in resource‐rich and resource‐poor soils and could unlock nature‐based pathways to raise carbon and nutrient retention for sustainable agriculture.

Integrated transcriptomic and functional analyses provide insights into the heat stress response mechanisms and HrcA mediated potential regulatory in Tetragenococcus halophilus JY1 - Fangming Lan; Yu Zhang; Chi Zhao; Jiayi Lin; Dongdong Sun; Juliang Dai; Lixin Luo (Food Bioscience, 2026)

Rhizosphere phosphorus and iron cycling accelerates manganese phytoextraction by Polygonum lapathifolium - Chijian Tang; Cuiping Wan; Jianing Gan; Ziang He; Caiping Wei; Haijiao Tan; Rifeng Wu; Fangming Yu; Yi Li (Journal of Hazardous Materials, 2026)

Optimisation of temperature sensing network deployment and prediction modelling of the active layer in Heilongjiang seasonally frozen ground during spring - Yu Zhang; Fangming Tian; Feng Tan (Biosystems Engineering, 2026)

Phosphate-solubilizing bacteria enhance cadmium phytoremediation by Solanum nigrum L. through improved phosphorus availability and cycling in contaminated soil - Shiyu Luo; Chijian Tang; Yong Shan; Cuiping Wan; Yinghao Mo; Yaoheng Huang; Rifeng Wu; Fangming Yu; Yi Li (Journal of Hazardous Materials, 2026)

Variations in microbial community structure and extracellular enzyme stoichiometry in heavy metal-contaminated soil under different fertilization regimes - Xian Huang; Shuting Tang; Xiaoming Xin; Lixing Chen; Xinying He; Yueying Huang; Fangming Yu; Yi Li (Applied Soil Ecology, 2025)

Phosphate-solubilizing bacteria facilitate rhizospheric processes of Bidens pilosa L. in the phytoremediation of cadmium-contaminated soil: Link between phosphorus availability and cadmium accumulation - Yi Li; Shiyu Luo; Yiyun Fu; Chijian Tang; Xiaoxiao Qin; Dongyi Shi; Wei Lan; Yingxuan Tang; Fangming Yu (Journal of Hazardous Materials, 2025)

Potential impacts of polyethylene microplastics and heavy metals on Bidens pilosa L. growth: Shifts in root-associated endophyte microbial communities - Ziang He; Yanxue Wang; Yiyun Fu; Xiaoxiao Qin; Wei Lan; Dongyi Shi; Yingxuan Tang; Fangming Yu; Yi Li (Journal of Hazardous Materials, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Dynamic impact of polyethylene terephthalate nanoplastics on antibiotic resistance and microplastics degradation genes in the rhizosphere of Oryza sativa L. - Yi Li; Weiwei Qin; Xiaomin Xin; Chijian Tang; Yueying Huang; Xinying He; Lixing Chen; Guo Yu; Fangming Yu (Journal of Hazardous Materials, 2025)

Unravelling the response mechanism of extracellular polysaccharides synthesis and salt stress resistance in Tetragenococcus halophilus JY1biofilm formation - Jiayi Lin; Chi Zhao; Jvliang Dai; Yu Zhang; Fangming Lan; Lixin Luo (Food Bioscience, 2025)

Nanovaccine enables complement system inhibition and high-dose AAV re-administration - Zhonghao Liao; Jiang Yu; Fangming Liang; Yubo Liu; Zhenyang Zhao; Yue Wang; Xianbao Shi; Yongjun Wang; Hongzhuo Liu (Chemical Engineering Journal, 2025)

Evidence that beneficial microbial inoculation enhances heavy metal-contaminated soil remediation: Variations in plant endophyte communities - Fangming Yu; Ziang He; Xiaomin Xin; Xinwei Shi; Lixing Chen; Xinying He; Yueying Huang; Yi Li (Journal of Hazardous Materials, 2024)

Recent advances in hydrogen process safety: Deflagration behaviors and explosion mitigation strategies - Peng Yang; Tao Wang; Yuhuai Sheng; Yingying Yu; Ruikang Li; Bin Su; Fangming Cheng; Jiao Qu; Jun Deng; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

Soil aggregate size mediates the variations in the abundance and function of ammonia oxidizers in heavy metal-contaminated soil under different nitrogen fertilization regimes - Xian Huang; Shuting Tang; Meng Zeng; Zhongkai Qin; Jialiang Liang; Yuyuan Chen; Yamei Wu; Shuairen Chen; Fangming Yu; Yi Li (Applied Soil Ecology, 2024)

Effect of polyethylene microplastics on antibiotic resistance genes: A comparison based on different soil types and plant types - Yi Li; Xinwei Shi; Meng Zeng; Peiqing Qin; Mingyue Fu; Shiyu Luo; Chijian Tang; Cuiju Mo; Fangming Yu (Journal of Hazardous Materials, 2024)

Experimental investigation and numerical analysis on the confined deflagration behavior of methane-air mixtures within the suppression of typical haloalkanes - Tao Wang; Yuhuai Sheng; Yingying Yu; Fangming Cheng; Xuhan Ding; Jiao Qu; Jun Deng; Fan Nan; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

Proteomics-based analysis on the stress response mechanism of Bidens pilosa L. under cadmium exposure - Yi Li; Xinwei Shi; Jie Xu; Xiaofang Huang; Jingpei Feng; Yuanyuan Huang; Kehui Liu; Fangming Yu (Journal of Hazardous Materials, 2024)

Investigation on the lower flammability limit and critical inhibition concentration of hydrogen under the influence of inhibitors - He Liang; Tao Wang; Zhenmin Luo; Jianliang Yu; Weizhai Yi; Fangming Cheng; Jingyu Zhao; Xingqing Yan; Jun Deng; Jihao Shi (Fuel, 2024)

Effects of polyethylene microplastics and heavy metals on soil-plant microbial dynamics - Yi Li; Xinwei Shi; Peiqing Qin; Meng Zeng; Mingyue Fu; Yuyuan Chen; Zhongkai Qin; Yamei Wu; Jialiang Liang; Shuairen Chen; Fangming Yu (Environmental Pollution, 2024)

Soil aggregate size mediates the impact of different fertilization patterns on the diazotrophic community of mine soils - Xian Huang; Shuting Tang; Meng Zeng; Yamei Wu; Jialiang Liang; Yue Yuan; Fangming Yu; Yi Li (Applied Soil Ecology, 2024)

Metagenomics reveals taxon-specific responses of soil nitrogen cycling under different fertilization regimes in heavy metal contaminated soil - Xinwei Shi; Weilan Tan; Shuting Tang; Qiujie Ling; Chijian Tang; Peiqing Qin; Shiyu Luo; Yinjun Zhao; Fangming Yu; Yi Li (Journal of Environmental Management, 2023)

Quantitative proteomic analysis of the mechanism of Cd toxicity in Enterobacter sp. FM-1: Comparison of different growth stages - Yi Li; Xinwei Shi; Yuyuan Chen; Shiyu Luo; Zhongkai Qin; Shuairen Chen; Yamei Wu; Fangming Yu (Environmental Pollution, 2023)

Metagenomics combined with metabolomics reveals the effect of Enterobacter sp. inoculation on the rhizosphere microenvironment of Bidens pilosa L. in heavy metal contaminated soil - Yi Li; Xinwei Shi; Weilan Tan; Qiujie Ling; Fengmei Pei; Shiyu Luo; Peiqing Qin; Huijian Yuan; Liuan Huang; Fangming Yu (Journal of Hazardous Materials, 2023)

Variations on the diazotrophic community in the rhizosphere soil of three dominant plant species in a lead–zinc mine area - Yi Li; Xuan Chen; Chijian Tang; Meng Zeng; Songying Li; Qiujie Ling; Kehui Liu; Jiangming Ma; Shuting Tang; Fangming Yu (Plant and Soil, 2023)

Potential impact of polyethylene microplastics on the growth of water spinach (Ipomoea aquatica F.): Endophyte and rhizosphere effects - Fangming Yu; Mingyue Fu; Chijian Tang; Cuiju Mo; Songying Li; Shiyu Luo; Peiqing Qin; Yinjun Zhao; Yi Li (Chemosphere, 2023)

Effect of N2 inerting on the inhibition of methane explosions by a multicomponent powder - Tenglong Zhao; Xiaokun Chen; Zhenmin Luo; Fangming Cheng; Kunlun Lu; Xueqiang Shi; Wencong Yu (Fuel, 2023)

CaFe-layered double hydroxide corn straw biochar reduced heavy metal uptake by Brassica campestris L. and Ipomoea aquatic F.: Rhizosphere effects and oxidative stress alleviation - Fangming Yu; Tiantian Gu; Jiayu Wei; Chijian Tang; Songying Li; Yuyuan Chen; Yanlan Su; Kehui Liu; Jiangming Ma; Xin Liang; Yi Li (Journal of Environmental Management, 2023)

Insights into the heavy metal adsorption and immobilization mechanisms of CaFe-layered double hydroxide corn straw biochar: Synthesis and application in a combined heavy metal-contaminated environment - Xin Liang; Yanlan Su; Xinnuo Wang; Chuntao Liang; Chijian Tang; Jiayu Wei; Kehui Liu; Jiangming Ma; Fangming Yu; Yi Li (Chemosphere, 2023)

A modified diatomite additive alleviates cadmium-induced oxidative stress in Bidens pilosa L. by altering soil microbial communities - Fangming Yu; Xin Liang; Yanying Li; Yanlan Su; Shuting Tang; Jiayu Wei; Kehui Liu; Jiangming Ma; Yi Li (Environmental Science and Pollution Research, 2023)

Impact of environmental factors on the ammonia-oxidizing and denitrifying microbial community and functional genes along soil profiles from different ecologically degraded areas in the Siding mine - Shuting Tang; Yin Rao; Shulian Huang; Yue Xu; Kaiyue Zeng; Xin Liang; Qiujie Ling; Kehui Liu; Jiangming Ma; Fangming Yu; Yi Li (Journal of Environmental Management, 2023)

Correction to: Publication characteristics, topic trends and knowledge domains of karst ecological restoration: a bibliometric and knowledge mapping analysis from 1991 to 2021 - Kehui Liu; Xiaojin Guan; Guangluan Li; Min Duan; Yi Li; Yanyan Hong; Meimei Lin; Rongxin Fu; Fangming Yu (Plant and Soil, 2022)

Publication characteristics, topic trends and knowledge domains of karst ecological restoration: a bibliometric and knowledge mapping analysis from 1991 to 2021 - Kehui Liu; Xiaojin Guan; Guangluan Li; Min Duan; Yi Li; Yanyan Hong; Meimei Lin; Rongxin Fu; Fangming Yu (Plant and Soil, 2022)

Characterization of plant growth-promoting traits of Enterobacter sp. and its ability to promote cadmium/lead accumulation in Centella asiatica L. - Yi Li; Lijuan Mo; Xiaoqin Zhou; Yawei Yao; Jiangming Ma; Kehui Liu; Fangming Yu (Environmental Science and Pollution Research, 2022)

Manganese Accumulation and Plant Physiology Behaviour of Camellia oleifera in Response to Different Levels of Phosphate Fertilization - Fangming Yu; Meifen Xin; Yawei Yao; Xueru Wang; Kehui Liu; Yi Li (Journal of Soil Science and Plant Nutrition, 2021)

Comparison of the diagnostic efficacy of the CapitalBio Mycobacterium real-time polymerase chain reaction detection test and Xpert MTB/RIF in smear-negative pulmonary tuberculosis - Hong Zheng; Fangming Zhong; Guocan Yu; Yanqin Shen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Hydrocotyle vulgaris L.: a new cadmium-tolerant landscape species and its physiological responses to cadmium exposure - Kehui Liu; Xiaolu Liang; Chunming Li; Leyi Wang; Xiaoyu He; Rilan Qin; Yi Li; Fangming Yu (Environmental Science and Pollution Research, 2021)

Enterobacter sp. FM-1 inoculation influenced heavy metal-induced oxidative stress in pakchoi (Brassica campestris L. ssp. Chinensis Makino) and water spinach (Ipomoea aquatic F.) cultivated in cadmium and lead co-contaminated soils - Fangming Yu; Yawei Yao; Jingpei Feng; Xueru Wang; Jiangming Ma; Kehui Liu; Yi Li (Plant and Soil, 2021)

Investigation of plant species and their heavy metal accumulation in manganese mine tailings in Pingle Mn mine, China - Kehui Liu; Haichun Zhang; Yufang Liu; Yi Li; Fangming Yu (Environmental Science and Pollution Research, 2020)

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Manganese tolerance and accumulation characteristics of a woody accumulator Camellia oleifera - Fangming Yu; Kehui Liu; Panhua Ye; Zhenming Zhou; Chaoshu Chen; Yi Li (Environmental Science and Pollution Research, 2019)

Concentrations and health risks of heavy metals in soils and crops around the Pingle manganese (Mn) mine area in Guangxi Province, China - Kehui Liu; Liuqun Fan; Yi Li; Zhengming Zhou; Chaoshu Chen; Bin Chen; Fangming Yu (Environmental Science and Pollution Research, 2018)

A disintegrin and metalloproteinase with thrombospondin motif 1 (ADAMTS1) expression increases in acute aortic dissection - Yanxiang Gao; Wenjing Wu; Changan Yu; Fangming Zhong; Geng Li; Wei Kong; Jingang Zheng (Science China Life Sciences, 2016)

Sr-Nd-Pb Isotopic compositions of the Neogene Eolian Deposits in the Xining Basin and Implications for Their Dust Sources - Fangming Zeng; Meiyan Liang; Shuzhen Peng; Dongmei Yu; Shuyuan Xiang (Journal of Earth Science, 2015)

Environmental evolution of the south margin of Qaidam Basin reconstructed from the Holocene loess deposit by n-alkane and pollen records - Shuyuan Xiang; Fangming Zeng; Guocan Wang; Jianxin Yu (Journal of Earth Science, 2013)